2017
DOI: 10.1302/2046-3758.62.bjr-2016-0225.r1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of all-suture anchors for rotator cuff repair

Abstract: ObjectivesAll-suture anchors are increasingly used in rotator cuff repair procedures. Potential benefits include decreased bone damage. However, there is limited published evidence for the relative strength of fixation for all-suture anchors compared with traditional anchors.Materials and MethodsA total of four commercially available all-suture anchors, the ‘Y-Knot’ (ConMed), Q-FIX (Smith & Nephew), ICONIX (Stryker) and JuggerKnot (Zimmer Biomet) and a traditional anchor control TWINFIX Ultra PK Suture Anchor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 21 publications
(46 reference statements)
0
54
3
1
Order By: Relevance
“…Before the inserter was removed, the insertion angle was cross-checked with a goniometer measuring the angle between the bone surface and the inserter of the anchor. A clamp to anchor distance of 10 cm was chosen, as previously published [20]. Since the load was not applied by the cuff muscle but by the threads aligned in their loading direction, the humeral head was protected by a plastic cover.…”
Section: Methodsmentioning
confidence: 99%
“…Before the inserter was removed, the insertion angle was cross-checked with a goniometer measuring the angle between the bone surface and the inserter of the anchor. A clamp to anchor distance of 10 cm was chosen, as previously published [20]. Since the load was not applied by the cuff muscle but by the threads aligned in their loading direction, the humeral head was protected by a plastic cover.…”
Section: Methodsmentioning
confidence: 99%
“…The authors compared 12 fresh-frozen human shoulders that underwent all suture anchors repair to 12 that underwent conventional anchors repair. They demonstrated that decreased failure load, increased total displacement, and variable failure mechanisms in all-suture anchors and also concluded that their findings will aid the surgeons choice of implant, in the context of the clinical scenario (14). In addition, compared to other conventional suture anchors, (9).…”
Section: Discussionmentioning
confidence: 95%
“…Although arthroscopic surgery suture anchors continue to evolve, the complications of bankart repair have not been completely solved (6,(20)(21)(22)(23). Metal suture anchor fixation is frequently used although it causes complications such as arthritis, pull-out, and osteolysis (10,11,14). Furthermore, several problems occur with anchor practice in labral repair (21,22).…”
Section: Discussionmentioning
confidence: 99%
“… 3 In particular, a growing interest has been recently focused on the biomechanical properties of different types of suture anchors used for rotator cuff repair concerning their stress resistance and suture configurations. 4 5…”
Section: Introductionmentioning
confidence: 99%